Comparative transcriptome analysis identifies genes associated with chlorophyll levels and reveals photosynthesis in green flesh of radish taproot. - Yuan-Yuan Li (Public Library of Science (PLoS), 2021)
The flesh of the taproot of Raphanus sativus L. is rich in chlorophyll (Chl) throughout the developmental process, which is why the flesh is green. However, little is known about which genes are associated with Chl accumulation in this non-foliar, internal green tissue and whether the green flesh can perform photosynthesis. To determine these aspects, we measured the Chl content, examined Chl fluorescence, and carried out comparative transcriptome analyses of taproot flesh between green-fleshed "Cuishuai" and white-fleshed "Zhedachang" across five developmental stages. Numerous genes involved in the Chl metabolic pathway were identified. It was found that Chl accumulation in radish green flesh may be due to the low expression of Chl degradation genes and high expression of Chl biosynthesis genes, especially those associated with Part Ⅳ (from Protoporphyrin Ⅸ to Chl a). Bioinformatics analysis revealed that differentially expressed genes between "Cuishuai" and "Zhedachang" were significantly enriched in photosynthesis-related pathways, such as photosynthesis, antenna proteins, porphyrin and Chl metabolism, carbon fixation, and photorespiration. Twenty-five genes involved in the Calvin cycle were highly expressed in "Cuishuai". These findings suggested that photosynthesis occurred in the radish green flesh, which was also supported by the results of Chl fluorescence. Our study provides transcriptome data on radish taproots and provides new information on the formation and function of radish green flesh.